2014
DOI: 10.1093/annonc/mdu165.212
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Colorectal Cancer: Serum LDH Levels Predict Survival in Metastatic Disease

Abstract: Introduction: Lactate dehydrogenase (LDH) is a product regulates the anaerobic transformation of pyruvate to lactate for energy acquisition. The significance of serum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Elevated levels of LDH in the blood can be indicative of tissue damage or disease, and have been associated with poor prognosis in several types of cancer 4,17,18 . Research has suggested that LDH levels can be a prognostic factor for CRC, especially in metastatic disease 5,19 . So far, prognostic models of survival have often relied on pretreatment baseline LDH, and very few models link survival to longitudinal LDH measured repeatedly over time during treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of LDH in the blood can be indicative of tissue damage or disease, and have been associated with poor prognosis in several types of cancer 4,17,18 . Research has suggested that LDH levels can be a prognostic factor for CRC, especially in metastatic disease 5,19 . So far, prognostic models of survival have often relied on pretreatment baseline LDH, and very few models link survival to longitudinal LDH measured repeatedly over time during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…4,17,18 Research has suggested that LDH levels can be a prognostic factor for CRC, especially in metastatic disease. 5,19 So far, prognostic models of survival have often relied on pretreatment baseline LDH, and very few models link survival to longitudinal LDH measured repeatedly over time during treatment.…”
Section: Articlementioning
confidence: 99%